A long shelf-life melon created via CRISPR/Cas9 RNP-based in planta genome editing - Sasaki, Kentaro; Urano, Kaoru; Mimida, Naozumi; Nonaka, Satoko; Ezura, Hiroshi; Imai, Ryozo (Frontiers in Genome Editing, 2025)
Genome editing in melon (Cucumis melo L.) remains a significant challenge due to the inefficiencies associated with conventional cell culture-based transformation methods. In the present study, a novel in planta Particle Bombardment (iPB) approach was developed to enable DNA-free genome editing in melon without the need for cell culture. CRISPR/Cas9 ribonucleoproteins (RNPs) were coated onto gold particles and delivered directly into shoot apical meristem tissue, which harbors potential germline cells, via particle bombardment. This method was applied to enhance fruit shelf-life by targeting an ethylene biosynthesis gene (CmACO1). The resulting cmaco1 mutant demonstrated a significantly extended shelf-life, attributable to reduced ethylene production during fruit ripening. This delayed ripening phenotype was reversed upon treatment with exogenous ethylene, confirming the functional impact of CmACO1 disruption. Because this strategy bypasses cell culture, the iPB-RNP method offers a solution to common limitations in genome editing, such as genotype dependence and somaclonal variation. Consequently, this technique holds substantial promise for advancing commercial melon breeding efforts and may be broadly applicable to other species within the Cucurbitaceae family.